Analysis of postdischarge interventions for children treated for moderate or severe wasting, growth faltering or failure, or edema - Bliznashka, Lilia; Rattigan, Susan B.; Sudfeld, Christopher R.; Isanaka, Sheila (American Medical Association, 2023)
Importance: Children treated for acute malnutrition remain at increased risk of relapse, infection, and mortality after programmatic recovery. Global guidelines for the management of acute malnutrition currently provide no recommendations to sustain recovery following treatment discharge. Objective: To inform guideline development by evaluating the evidence on postdischarge interventions to improve outcomes within 6 months after discharge. Evidence: Review In this systematic review, 8 databases were searched from inception through December 2021 and included randomized and quasi-experimental studies investigating interventions delivered after discharge from nutritional treatment for children aged 0 to 59 months. Outcomes were relapse, deterioration to severe wasting, readmission, sustained recovery, anthropometry, all-cause mortality, and morbidity within 6 months after discharge. The risk of bias was assessed using Cochrane tools, and the certainty of the evidence was evaluated with the GRADE approach. Findings: Of 7124 records identified, 8 studies, conducted in 7 countries between 2003 and 2019 with 5965 participants, were included. The study interventions included antibiotic prophylaxis (n = 1), zinc supplementation (n = 1), food supplementation (n = 2), psychosocial stimulation (n = 3), unconditional cash transfers (n = 1), and an integrated biomedical, food supplementation, and malaria prevention package (n = 1). Risk of bias was moderate or high for half the studies. Only unconditional cash transfers were associated with reduced relapse, while the integrated package was associated with improved sustained recovery. Zinc supplementation, food supplementation, psychosocial stimulation, and unconditional cash transfers were associated with improvements in postdischarge anthropometry, while zinc supplementation was associated with reductions in multiple postdischarge morbidities. Conclusions and Relevance: In this systematic review of postdischarge interventions to reduce relapse and improve other postdischarge outcomes among children treated for acute malnutrition, evidence was limited. Biomedical, cash, and integrated interventions showed promise in improving certain postdischarge outcomes for children treated for moderate or severe acute malnutrition in single studies. Further evidence on the efficacy, effectiveness, and operational feasibility of postdischarge interventions in other contexts is needed to inform global guidance development.